2016
DOI: 10.1002/chem.201603255
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Level Characterization of the Structure and Interactions in Peptide‐Functionalized Metal–Organic Frameworks

Abstract: We use DFT, newly parameterized Molecular Dynamics simulations and last generation 15 N DNP surface enhanced solid-state NMR spectroscopy to understand graft-host interactions and effects imposed by the MOF host on peptide conformations in a peptide-functionalized MOF. Focusing on two grafts typified by MIL-68-Proline (-Pro) and MIL-68-Glycine-Proline (-Gly-Pro), we identified the most likely peptide conformations adopted in the functionalized hybrid frameworks. We found that hydrogen bond interactions between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 93 publications
0
21
0
Order By: Relevance
“…Such diffusion has been monitored by EPR spectroscopy and the estimate of 13 C- 27 Al dipolar couplings in aluminium-based MOF has demonstrated that the impregnation with a radical solution and the freezing of the sample down to 100 K do not alter the particular MOF's structure [239]. For bulkier PAs, such as TEKPol, or functionalized MOFs, the PAs cannot penetrate the pores and reside on or near the surface of the crystallites [111][112][113]264]. DNP-enhanced 1 H polarization is transported within the microcrystal by spin diffusion among protons of the linker and the solvent.…”
Section: Microporous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such diffusion has been monitored by EPR spectroscopy and the estimate of 13 C- 27 Al dipolar couplings in aluminium-based MOF has demonstrated that the impregnation with a radical solution and the freezing of the sample down to 100 K do not alter the particular MOF's structure [239]. For bulkier PAs, such as TEKPol, or functionalized MOFs, the PAs cannot penetrate the pores and reside on or near the surface of the crystallites [111][112][113]264]. DNP-enhanced 1 H polarization is transported within the microcrystal by spin diffusion among protons of the linker and the solvent.…”
Section: Microporous Materialsmentioning
confidence: 99%
“…Hence, the DNP enhancements for MOFs are in general significantly lower than those achieved for mesoporous materials. Nevertheless, the gain in sensitivity provided by DNP has enabled the detection of insensitive isotopes, such as 15 N in natural abundance [111,113,264] or 195 Pt [112], in MOFs. DNP has also been employed for the characterization of zeolite frameworks [114][115][116]194] and the organic species in its micropores [117,266,267].…”
Section: Microporous Materialsmentioning
confidence: 99%
“…In addition to SPPS, microwave‐assisted postsynthetic methods have recently been reported on grafting oligopeptides onto MOF backbones under microwave irradiation, yielding enantiopure peptides anchored within MOF cavities . Simulation work was also carried out to study the conformation of peptides when grafted in MOF hosts; which specific conformational selection is identified as a result of strong host‐guest interactions …”
Section: Incorporation Of Small Biomoleculesmentioning
confidence: 99%
“…Due to the aggregation effect of bare NMOFs, proper surface modification is needed to improve the water dispersibility or various further functionalization of NMOFs for biomedical applications. NMOFs can be coated with silica, 27 peptides, 28 , 29 proteins, 26 , 30 polymers, 31 etc. Although great progress has been made, functionalization on the surface of NMOFs and further conjugation with molecular probes is still very challenging.…”
Section: Introductionmentioning
confidence: 99%